Residual stress relaxation of shot-peened 2024-T351 aluminium alloy - Zaroog, Omar Suliman (2011)
Near surface tensile residual stresses tend to accelerate the initiation and growth phases of the fatigue process while compressive residual stresses close to a surface may prolong fatigue life and consider as beneficial residual stresses. Shot peening process used to induce beneficial compressive residual stress in materials. However, the residual stresses may relax due to thermal, static mechanical load and cyclic load. Even with partial relaxation, there found a beneficial effect of compressive residual stress on fatigue life. The problem is how much is the relaxation? To answer this question a 2024 T351 aluminium alloy specimens were shot peened into three shot peening intensities 0.0054 A, 0.0067 A and 0.009 A. The cyclic test for the two loads magnitude, 15.5 kN and 30 kN, was performed for the 1, 2, 10, 1000 and 10000 cycles. The initial residual stress and residual stress as well as cold work after each cyclic load were measured for the three shot peening intensities and for the two magnitudes of loads using X-ray diffraction method. Initial and after microhardness of each cyclic load were measured for the three shot peening intensities. The results showed that the most relaxation of the initial residual stress took place in the first cycle; the initial residual stress was relaxed by 46% after first cycle in the load 30 kN and shot peening intensity of 0.0054 A. Relaxation of residual stresses occurred within first loading cycles were increasing with increasing loading stress amplitude and due to quasi-static relaxation effects. The residual stress after the first cycle found to relax depends on the load amplitude. The maximum relaxation found is 54% of the initial residual stress in the shot peen intensity of 0.0054 A after 10000 cycles for the load of 30 kN. The changed in the relaxation percentages of all specimens from 10 cyclic load to 10000 cyclic load is in the range of 5-8% of the initial residual stress. Microhardnesses were found to decrease depending on the load amplitude. A load of 30 kN made microhardness in the specimens decrease more than the 15.5 kN load. The microhardness was reduced by 39%, given a shot peen intensity of 0.009 A after 10000 cycles under a load of 30 kN. From observations and results, empirical equations to estimate the residual stress relaxation were proposed. The equations incorporated the number of cycles and cold work to predict the amount of residual stress relaxation. Finally, the results of the estimation are in a good agreement with experimental data.